The Impact of 30-Minute Jogging Before Iftar on University Students' Mood States During in Ramadan - Wulandari, Fifit Yeti; Priambodo, Anung (UNIVERSITAS NEGERI MAKASSAR, 2025)
This study investigates the impact of 30-minute aerobic exercise before iftar on the mood states of university students during Ramadan. Fasting during Ramadan poses physiological and psychological challenges, including fatigue, irritability, and decreased mood. While previous studies have explored the negative impacts of fasting on mood, limited research has focused on the potential benefits of aerobic exercise in alleviating these effects. A total of 21 male university students aged 18-23 (mean age = 19.0 years), with a mean body weight of 57 ± 7.39 kg and a mean height of 163.76 ± 7.45 cm, participated in this study. They engaged in moderate-intensity jogging (60-70% of their maximum heart rate) for 30 minutes, three times per week, during Ramadan. The Profile of Mood States (POMS) questionnaire was used to measure mood changes across six subscales: tension, anger, fatigue, depression, vigor, and concentration. The Shapiro-Wilk test confirmed normality of the data, and One-Way ANOVA was used to assess significant mood changes. The results showed significant reductions in negative mood states such as tension, anger, fatigue, and depression, and a notable increase in vigor. Conditions such as tension, anger, fatigue, and depression, as well as a significant increase in enthusiasm. Not only that, there is an increase in concentration. The findings of this study indicate that doing aerobic exercise before breaking the fast can improve mood and concentration well during the Ramadan fast, so this exercise offers a practical solution to support the mental and physical health of fasting students.